The Quality of Sleep, Mood Stability and Coping Strategies Among House Officers (Medical Forum Monthly, 2024)
Objective: To look into the relationship between quality of sleep, mood stability and coping strategies among house officers.Study Design: Cross sectional studyPlace of Study: This study was conducted at Jinnah Hospital, Ganga Ram Hospital, Lady Wallington Hospital and Mayo Hospital, Lahore for a period of one month.Materials and methods: The sample comprised 120 male and female salaried House Officers working in five public sector hospitals in Lahore. The Pittsburgh Sleep Quality Index, Brunel Mood Scale, and the Proactive Coping Inventory were used for data collection.Results: The study yielded interesting relationships; a strong positive correlation was found between mood stability and sleep quality. The number of hours that the respondents worked in a day on average was positively, though weakly, correlated with mood stability. A positive though weak relationship between mood stability and sleep quality was observed. Mood stability and hours of sleep were found to be significantly negatively correlated. The results are in many ways similar to findings reported by researchers in the developed countries. This study has highlighted some factors that might affect the physical and psychological well being of new entrants into a profession. The findings can be helpful in devising strategies for improving quality of such professionals’ life as well as their performance by improving their sleep quality as well as proactive coping strategy most appropriate for them.Conclusion: The correlation between sleep quality, mood stability, and coping strategies may have significant implications and may impact young medical professionals’ performance. Their performance may be enhanced optimally by considering these variables in assigning duties and responsibilities.